CONSUMER DECISION TOWARDS ONLINE SHOPPING AND CONSUMER PRIMARY WAY OF SHOP IN COMPARISON WITH BRICK AND MORTAR STORE - Baisa, Roidah Lukman; Thoyib, Armanu (Jurnal Ilmiah Mahasiswa FEB, 2013)
Online Shopping is trending since past few years, providing niche for small retailer. This research is analyzing about  factors influence consumer decision towards online shopping, greatest factor influence consumer decision to shop online and what is consumer primary way of shop, online or visiting brick and mortar. Online shop in this study is specifed to those operated by small retailer that usually using social media as platform  such as KasKus, Facebook, Multiply, and BlackBerry Messenger. There are five factors that influence consumer decision to shop online that used as independent variable in this study, those is convinience, amount of information, price, limitation, and security, and consumer decision as dependent variable. In order to finding influence of independent variables towards dependent variable, research method used in this study is multiple reggression analysis with three clasical assumption test: normalty, multicollinearity, and heteroscedaticity. Method used in gathering data is questionnaire with undergraduate student in Faculty of Economic and Business Brawijaya University who has experienced shopping online before as population and 100 person who fulfill the criteria is choosed as sample (non random sampling). The result of this study is that each element used as independent variable significantly affecting consumer decision (dependent variable) and security is the factor with greatest influence. Conclusion in this study is that consumer decision towards online shopping is affected significantly by convinience, amount of information, price, limitation, and security. Greatest factor that influence consumer decision to shop online is security, second is price, third is convinience, followed by limitations, and lastly consumer also considering amount of information, and visiting brick and mortar store still become consumer primary way of shopping compared by shopping online eventhough all respodent has experienced online shopping before. Keywords  : online shopping, online shop,  brick and mortar, consumer decision, maketing strategy, retailing.